Bookreview: Christianizing South CHINA: Mission, Development, and Identity in Modern Chaoshan - ZHU, Xiaoye (Journal of Research for Christianity in China (JRCC), 2025)
Bookreview: Christianizing South CHINA: Mission, Development, and Identity in Modern Chaoshan